Classification of a member in terms of healthcare risk - A. De Villiers; C. A. Van Der Merwe; T. J. Van Wyk Kotze (South African Journal of Business Management, 2004)
Legislation by government has changed the playing fields in the medical scheme industry in South Africa. Medical schemes can no longer choose their members or discriminate against members who claim more than projected amounts. Only those medical schemes that are able to manage their risk optimally, will ultimately survive.In the research it was established that the number of chronic beneficiaries in a family is an important risk factor if a member is classified into a normal claim category or an above-normal claim category. The medical schemes should make sure that they have systems in place to manage the health of such beneficiaries holistically. This group of individuals is ideally suited for a preventative healthcare programme.
Keywords: 650